Investigation of the effect of some plant aqueous extracts on calcium phosphate precipitation as a simulation of initial dental calculus formation in vitro - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2020)
Background and Aims: Calcium phosphate is most of the inorganic content of dental calculus. Therefore, knowing or controlling the precipitation mechanism of calcium phosphate is very important for the inhibition of dental calculus formation at the beginning. Plants have been known to be excellent sources of many nutritional and phytochemical content. The aim of this study is to investigate the effects of Petroselinum crispum, Eruca vesicaria ssp. sativa, Beta vulgaris L.var.cicla, Rumex cristatus DC. and Cotinus coggygria Scop. aqueous extracts on calcium phosphate precipitation, which is thought to reflect the onset of dental calculus formation in vitro. Methods: The optical density (0D) increases first with the calcium phosphate nucleation and when the balance is reached, the optical density decreases gradually when the nuclei begin to aggregate and precipitate. The OD change was monitored by recording the absorbance at 620 nm. Results: The effect on the calcium phosphate precipitation varied differently among the 5 types of aqueous extracts. The smoke tree (Cotinus coggygria Scop.) extract activated calcium phosphate precipitation while all others inhibited precipitation. Conclusion: These results suggest that some types of plant aqueous extracts may have protective potential against dental calculus initially and, therefore they may be used in toothpastes or in mouthwashes.
Keywords: Dental calculus; calcium phosphate precipitation; plant aqueous extract; ANTIBACTERIAL ACTIVITY; ANTIOXIDANT ACTIVITY; SUPRAGINGIVAL; POLYPHENOLS; PREVENTION; FRACTIONS; LEAVES; WILD